2013
DOI: 10.1111/tbj.12071
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Vinorelbine for the Treatment of Breast Cancer

Abstract: The purpose of this study was to investigate the efficacy and safety profile of vinorelbine-based chemotherapy in different settings for the treatment of breast cancer. We performed a computerized search using combinations of the following keywords: "breast cancer", "breast neoplasms", "trial", "vinorelbine" and "navelbine". A total of 20 trials were included in this analysis, with a total of 5,080 patients accrued. Taxane was associated with enhanced overall survival (OS; p = 0.027) and response rate (RR; p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 35 publications
1
35
0
2
Order By: Relevance
“…Breast cancer is one of the most heterogeneous tumors, presenting various histologies, behaviors and outcomes (1)(2)(3)(4)(5). Patients with similar clinicopathological characteristics can have markedly different outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is one of the most heterogeneous tumors, presenting various histologies, behaviors and outcomes (1)(2)(3)(4)(5). Patients with similar clinicopathological characteristics can have markedly different outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…NVB has been evaluated in NSCLC in the adjuvant and advanced settings as a single agent and in combination with other agents (typically a platinum or gemcitabine) with modest success (16). In the present study, we detected the effects of combination of TRAIL and NVB on A549 cells and lung carcinoma-xenograft nude mice.…”
Section: Discussionmentioning
confidence: 79%
“…Oral formulations are not currently available for use in North America. Phase ii trials of vinorelbine have demonstrated varied rrs in the abc setting (25%-47%), depending on the line of therapy 84,85 .…”
Section: Vinorelbinementioning
confidence: 99%